SOLUTIONS FOR DEVELOPMENT OF SMART EDUCATION IN THE CURRENT SITUATION OF VIETNAM - Le Khanh Tuan (Izdevnieciba "Baltija Publishing", 2021)
Based on the determination of the connotation of smart education, and requirements on the conversion from traditional education to smart education, this article would like to estimate the number of works for building and developing smart education. From that, the article will identify difficulties and challenges, and propose solutions for the development of the smart education to the management levels from the schooling management to education and training authorities in the current situation of Vietnam.